A New Dead-time Compensation Method Based on LMS Algorithm for PMSM - Zhu, Hongguan; Chen, Ying; Lei, Hongdan; Chen, Dongdong; Li, Zongwei (Journal of physics. Conference series, 2021)
This paper presents a new dead-time compensation method for permanent-magnet synchronous motor (PMSM) at low speed. Based on least-mean-square (LMS) algorithm and combined with the traditional average voltage compensation method, the proposed method can determine the current polarity through extracting the fundamental current. Compared with traditional compensation methods, the proposed method can detect current polarity more accurately at low speed due to the narrower notch bandwidth. Moreover, this method is robust to motor parameters and easy to implement. The proposed method is simulated in a voltage-source inverter PMSM drive controlled by I/F and the results show that it meets the requirement of dead-time compensation and eliminates the influence of dead-time effect.